TEST CONTENT FORMALDEHYDE AND BORAX IN MEATBALLS SAMPLES SOLD IN ENVIRONMENT UNIVERSITY CAMPUS MUHAMMADIYAH SURAKARTA - Retno Setyaningsih; Muhammad Nurhadi; Dyah Susilowati (STIKES DUTAGAMA KLATEN, 2017)
Background: Borax and formaldehyde are prohibited from use in food, but it is still found in some products such as noodles and meatballs. Borax and formaldehyde content test can be done using a flame test methods and test methods color. Purpose: To find meatballs sold in Surakarta Muhammadiyah University campus environments containing borax and formaldehyde. Research Method: This study is a descriptive survey with cross sectional design and sampling technique used purposive sampling. The sample in this study amounted to 8 (eight) where each stall investigated two (2) pieces of meatballs. Result: Borax and formaldehyde content test on the sample meatballs sold in Surakarta Muhammadiyah University campus environment using a flame test methods and test methods showed color negative or undetectable samples contain borax and formaldehyde. Conclusion: All of the samples tested meatballs that do not contain harmful preservatives, namely borax and formaldehyde. Meatball samples so it meets the requirements in Permenkes No. 033 Year 2012 on Food Additives.